Medicinal plants research in Asia: Volume I: The framework and project workplans - Batugal, P.A.; Kanniah, J.; Sy, L.; Oliver, J.T. (2004)
Medicinal plants address not only the need for access to medicine as a component of health services but also to the need for increased income for farmers and as a significant contribution to the national economy. And, yet, a basic foundation to effectively bring about these contributions is to be able to collect, characterize, evaluate the genetic resources that a country has from animals, plants, insects and microorganisms which can serve this purpose. While there have been constraints in exchanges of materials and technology for pharmaceuticals derived from biological organisms, largely because of its very significant commercial value and questions on intellectual property rights, there is no doubt that a critical human need such as access to medicine which determines quality of life of human society will remain as a concern that will require a concerted effort among countries and peoples all over the world. It is in this spirit that the International Plant Genetic Resources Institute (IPGRI), which is one of the 15 international research centres of the Consultative Group on International Agriculture Research (CGIAR) and the Rural Development Administration (RDA) of the Republic of Korea embarked on a joint research collaboration on ”Inventory and Documentation of Medicinal Plants in the Asia Pacific Region” involving 14 countries. This proceedings is a result of the first stakeholder meeting of the countries and institutions involved in the project. It is a combination of reports on the framework of the project, the status report of countries on their medicinal plant programme, the agreements among the participants during this meeting in terms of priority project activities and the different country research proposals on medicinal plants.